Pengaruh Konten TikTok terhadap minat belajar pada Gen Z - Ilham Muhamad Yasin; Lilis Karyawati; Abdul Azis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
TikTok is one of the most widely used social media platforms among Generation Z. The diverse content available, ranging from entertainment to education, can influence users' learning behavior and interest. This study aims to analyze the influence of TikTok content on learning interest among Generation Z. The research method used was a quantitative survey approach. Data were obtained by distributing questionnaires to respondents belonging to the Generation Z category and actively using the TikTok app. The collected data were analyzed using statistical analysis techniques to determine the relationship between the intensity of exposure to TikTok content and respondents' learning interest. The results indicate that TikTok content influences Generation Z's learning interest. Educational content can increase curiosity, motivation, and interest in learning materials, while excessive consumption of entertainment content has the potential to reduce learning focus and effective time management. Therefore, wise and selective use of TikTok is crucial so that this platform can become a learning support medium, not just a means of entertainment.